1995
DOI: 10.1093/infdis/172.2.595
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation among Pneumocystis carinii hominis Isolates in Recurrent Pneumocystosis

Abstract: Pneumocystis carinii hominis is a ubiquitous organism that causes pneumonia in immunocompromised persons. Paired P. carinii hominis isolates from human immunodeficiency virus-infected persons who had two episodes of pneumocystosis were examined for genetic heterogeneity. Genetic variation was detected by sequence comparison of a portion of the mitochondrial ribosomal RNA gene. In 5 of 10 patients experiencing two episodes of pneumocystosis, genetically distinct isolates were associated with each episode. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
96
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(103 citation statements)
references
References 10 publications
6
96
0
1
Order By: Relevance
“…The ITS1 and ITS2 regions evolve more rapidly than the functional domains that they flank and are therefore potentially more useful at demonstrating differences among closely related populations of organisms (4). The ITS region has also been used to examine differences in P. carinii isolates from different parts of the world (13) and from patients with recurrent episodes of PCP (10,23). The high level of variation in the ITS genes compared to those in other genes used for typing (e.g., the mitochondrial large-subunit [mt LSU] rRNA gene) demonstrates the utility of this genetic locus in epidemiologic studies and in the detection of genetic diversity.…”
mentioning
confidence: 99%
“…The ITS1 and ITS2 regions evolve more rapidly than the functional domains that they flank and are therefore potentially more useful at demonstrating differences among closely related populations of organisms (4). The ITS region has also been used to examine differences in P. carinii isolates from different parts of the world (13) and from patients with recurrent episodes of PCP (10,23). The high level of variation in the ITS genes compared to those in other genes used for typing (e.g., the mitochondrial large-subunit [mt LSU] rRNA gene) demonstrates the utility of this genetic locus in epidemiologic studies and in the detection of genetic diversity.…”
mentioning
confidence: 99%
“…Most cases are supposedly due to the reactivation of latent infections, but recent studies indicate the possibility of de novo introduction from human or environmental reservoirs (6,8).…”
mentioning
confidence: 99%
“…Sequence analysis of some genetic loci demonstrated a marked heterogeneity of P. carinii isolated from humans or other mammalian species (6,10,11,14,15,16,19,21). Coinfection with different strains of P. carinii in the same host has also been demonstrated (1,5,11,15,20).…”
mentioning
confidence: 99%
“…Research employing molecular techniques has also shown evidence of reinfection. By examining patients who have suffered from pneumocystosis several times, different genetic types of P. jirovecii were isolated at subsequent stages of the disease (Keely et al 1995). Furthermore, it has been noted that the genetic pattern of Pneumocystis isolated from infected people is not similar to the pattern characteristic for isolates collected at their place of birth, but is more often in accordance with the pattern characteristic for the place in which the person resided at the time of collection of the specimen (Beard et al 2000).…”
Section: Introductionmentioning
confidence: 99%